Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.4149/neo_2018_180731n559
|View full text |Cite
|
Sign up to set email alerts
|

Two Czech patients with familial adenomatous polyposis presenting mosaicism in APC gene

Abstract: During standard molecular diagnostic procedure, two Czech families with APC (Adenomatous polyposis coli gene) mosaicism have been detected. A woman with attenuated familial adenomatous polyposis (AFAP, OMIM #175100) was recently inspected by next generation sequencing. Standard bioinformatics pipeline, restricted to variants with at least 20% of reads (for germline variants) would miss mutation p.G1412X (NM_000038.5) present in 17% of reads. This novel variant was not present in any of her two children. Anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…These studies identified deep intronic APC variants that result in pseudoexon formation [ 19 , 20 ]. Through the use of sensitive techniques, somatic APC mosaicism has been demonstrated in a minority of adenomatous polyposis patients [ 21 26 ]. In addition, using deep sequence analysis of APC in DNA isolated from multiple adenomas, mosaic variants were identified in 9 of 18 patients with 21 to 100 adenomas; in some of these cases, NGS also detected the variants in leukocyte DNA at low frequency [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies identified deep intronic APC variants that result in pseudoexon formation [ 19 , 20 ]. Through the use of sensitive techniques, somatic APC mosaicism has been demonstrated in a minority of adenomatous polyposis patients [ 21 26 ]. In addition, using deep sequence analysis of APC in DNA isolated from multiple adenomas, mosaic variants were identified in 9 of 18 patients with 21 to 100 adenomas; in some of these cases, NGS also detected the variants in leukocyte DNA at low frequency [ 27 ].…”
Section: Introductionmentioning
confidence: 99%